2022
DOI: 10.18295/squmj.10.2022.059
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Utilisation, Experiences and Satisfaction with Postnatal Follow-up Care

Abstract: Postnatal follow-up care is reported to be the ‘underutilised’ aspect of the maternity care continuum. This review explores women’s utilisation of early and late postnatal follow-up and their experiences and satisfaction with it. Five online databases were searched for English or Arabic articles published between 2011 and 2021. Methodological quality of included studies was assessed using the Mixed Methods Appraisal Tool; the Andersen healthcare utilisation model was the framework for data analysis. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…The interview guide (Table 3) developed by the researchers was guided by the findings from the literature review. 13 Ethical approval was granted by the…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The interview guide (Table 3) developed by the researchers was guided by the findings from the literature review. 13 Ethical approval was granted by the…”
Section: Designmentioning
confidence: 99%
“…A literature review was undertaken with factors identified that impeded utilisation of postnatal follow-up, including women's lack of knowledge of postnatal services, beliefs that there is no need for postnatal follow-up and the impact of long queues (waiting time) at health centres. 13 Of the 17 studies eligible for inclusion in the review, one was conducted in the Middle East (Jordan), which has cultural similarities to Oman but a different healthcare system and delivery of postnatal care. This study reported concerns regarding the unmet learning needs of women in terms of postnatal care, including danger signs post caesarean section, breastfeeding and newborn care at the two postnatal contacts, that is, at Day 1 and 6-8 weeks following birth.…”
Section: Introductionmentioning
confidence: 99%
“…We designed and validated the fxVFA platform for the simultaneous quantification of three biomarkers of cardiac injury, namely, myoglobin, creatine kinase‐MB (CK‐MB), and heart‐type fatty acid binding protein (FABP). [ 64 ] These markers are present in cardiac muscle and become elevated in the blood flow after acute myocardial infarction (AMI). [ 64 ] Typical reference ranges of these three markers in healthy individuals are 20–80 ng mL −1 for myoglobin, [ 65 ] 5–10 ng mL −1 for CK‐MB, [ 66 ] and 1–5 ng mL −1 for FABP, [ 67 ] making them challenging targets for colorimetric detection.…”
Section: Introductionmentioning
confidence: 99%
“…Myoglobin and FABP are released after 1.5 h from symptoms onset, have a peak concentration after 4–9 h and might return to normal within 24 h. Both proteins are also present in skeletal muscles and therefore positive detection (i.e., >80 ng mL −1 for myoglobin and >5 ng mL −1 for FABP) by itself should be used with caution for diagnosis of AMI since noncardiac events can also cause their elevation. [ 64,65,67 ] CK‐MB is an isoenzyme of creatine kinase present in the heart muscle and has optimal diagnostic performance for AMI in the period of 6–26 h; however, it also becomes elevated after other cardiac pathologies (e.g., congestive cardiac failure), severe muscle damage (e.g., skeletal muscle disorders), and intake of drugs. [ 64 ] Therefore, the diagnosis of AMI based on the elevation of these three cardiac markers alone is risky; however, repeated negative tests in the relevant time intervals can be used to rule out AMI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation